Perubahan Perladangan menjadi Perkebunan dan Dampaknya terhadap Kebakaran Hutan dan Lahan di Provinsi Riau - Efral Derik (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2019)
Swidden agriculture is often associated on forest and land fires. Meanwhile, swidden agriculture do not always cause forest and land fires because the community applied their local knowledge. This study aim to describe the changes of swidden agriculture practices to plantation, and explain the impact of the swidden agriculture and plantation practice on forest and land fires in Riau Province. Theory of cultural change dan theory of innovation adoption were used to explain it. Survey method was used in this study. The data were collected from interview techniques, observation and recording of secondary data from various sources. The results of this study show that law enforcement is the main reason in the technological changes. The results of this study also indicate that forest and land fires were not caused by swidden agriculture. In other words, swidden agriculture did not cause forest and land fires.